Analisis Pengunaan Metode Ceramah dalam Meningkatkan Pemahaman Siswa pada Mata Pelajaran Akidah Akhlak di MI Hidayatus Shibyan - Mar'atus Sholihah; Adibah Junnah Rohmah; Moh. Rif'an Nur Alif (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
This research aims to analyze the use of the lecture method in teaching Akidah Akhlak at MI Hidayatus Shibyan. Along with the importance of religious education in shaping students' character, the lecture method is often used by teachers as an effective method of delivering material. This research uses a descriptive qualitative approach with the research subjects namely Aqidah Akhlak subject teachers. Data collection was carried out through observation, interviews and documentation. The data analysis technique used is the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The research results show that the lecture method, even though it has been used for a long time, is effective in conveying Akidah Akhlak material to students, especially if supported by the use of media such as a projector. However, the main challenge faced is keeping the attention of students who are easily distracted. To overcome this, teachers use ice-breaking techniques and more dynamic approaches, such as reading and listening together. Although the lecture method is effective, its success is highly dependent on the teacher's ability to manage the class and incorporate other interactive methods to increase student understanding and engagement. This research shows the importance of varied approaches in applying the lecture method to achieve optimal learning outcomes.